2015
DOI: 10.1002/jbm.b.33432
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional printed PCL‐hydroxyapatite scaffolds filled with CNTs for bone cell growth stimulation

Abstract: A three-phase [nanocrystalline hydroxyapatite (HA), carbon nanotubes (CNT), mixed in a polymeric matrix of polycaprolactone (PCL)] composite scaffold produced by 3D printing is presented. The CNT content varied between 0 and 10 wt % in a 50 wt % PCL matrix, with HA being the balance. With the combination of three well-known materials, these scaffolds aimed at bringing together the properties of all into a unique material to be used in tissue engineering as support for cell growth. The 3D printing technique all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(121 citation statements)
references
References 47 publications
(108 reference statements)
1
110
1
2
Order By: Relevance
“…On the other hand, the scaffold showed electrical conductivity of up to ≈2350 S/m −1 which is higher than that of many recently reported polymer based conductive composites (maximum < 100 S/m −1 ) suitable for 3D printing [84]. Gonçalves et al [85] demonstrated that a 3D printed nanocomposite scaffold system possesses enough compressive strength and electrical conductivity along with bioactivity, biocompatibility, porosity, and pore size which could be a suitable option for the application in the field of bone regenerative medicine. The scaffold was printed from three-phase monocrystalline hydroxyapatite (HA)/CNTs/PCL system with optimum viscosity.…”
Section: Processing Of Carbon Cnt/polymer Nanocomposites Using 3dpmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, the scaffold showed electrical conductivity of up to ≈2350 S/m −1 which is higher than that of many recently reported polymer based conductive composites (maximum < 100 S/m −1 ) suitable for 3D printing [84]. Gonçalves et al [85] demonstrated that a 3D printed nanocomposite scaffold system possesses enough compressive strength and electrical conductivity along with bioactivity, biocompatibility, porosity, and pore size which could be a suitable option for the application in the field of bone regenerative medicine. The scaffold was printed from three-phase monocrystalline hydroxyapatite (HA)/CNTs/PCL system with optimum viscosity.…”
Section: Processing Of Carbon Cnt/polymer Nanocomposites Using 3dpmentioning
confidence: 75%
“…The applications of the polymer/CNT nanocomposites include energy storage devices like microsupercapacitors, electronic components such as transducers, flexible conductor, emitters, and radio frequency inductors, absorber of electromagnetic energy, liquid sensors such as gas or strain sensors, precise electrical micro-interconnectors in 3D circuits and so on. High electrically conductive polymer/CNT nanocomposites can be beneficial as the 3D printable biomaterials electrical stimuli to enhance the cell functions [85]. As significant improvement in electrical conductivity is observed at very low CNT loading, 3D printed precise macro and micro-structured CNT/polymer nanocomposites could be a light weight, low cost and highly effective option for particular applications.…”
Section: Applicationsmentioning
confidence: 99%
“…Computer aided design and manufacturing (CAD/CAM) permits scaffold designs of any shape, size, and porous design, down to micrometer level resolution (Figure ). Even though 3D printing has been used in biomedical research for over a decade, robust bone regenerative outcomes have not been achieved until recently (Brunello et al, ; Cai, Xi, & Chua, ; Castilho et al, ; Cooke, Fisher, Dean, Rimnac, & Mikos, ; Cox, Thornby, Gibbons, Williams, & Mallick, ; Farzadi, Solati‐Hashjin, Asadi‐Eydivand, & Osman, ; Gonçalves et al, ; Hollister et al, ; Luo et al, ; Provaggi, Leong, & Kalaskar, ; Seitz, Rieder, Irsen, Leukers, & Tille, ; Wang, Schröder, & Müller, ; Xinning et al, ; Yao et al, ; Zhou, Buchanan, Mitchell, & Dunne, ). The paucity of promising translational outcomes is attributed to 3D printing approaches that do not leverage the principles of bone healing gleaned from endosteal implant bone healing.…”
Section: Advances In Materials Sciencementioning
confidence: 99%
“…Hydroxyapatite (HA) is a primary component in human teeth and bones. It, along with its analogues tricalcium phosphate (TCP) and calcium phosphate (CaP), has been printed into bone scaffolds with biomimetic structures, adequate mechanical strength, and the ability to promote osteogenesis …”
Section: Material/cells In 3d Bioprinting: From Bioink To Modular Buimentioning
confidence: 99%